Application and Development Prospects of Dietary Fibers in Flour Products. (16th March 2017) - Han, Wen; Ma, Sen; Li, Li; Wang, Xiao-xi; Zheng, Xue-ling
Abstract : Dietary fibers are often characterized by high nutritional quality, as they are able to cure many chronic diseases and improve texture, sensory characteristics, and shelf life of foods. Here, the following aspects of dietary fibers have been reviewed: nutritional properties, including the ability to regulate blood sugar levels, effects on microorganisms, antioxidant effect, potential role in losing weight, ability to regulate blood lipids, application in flour products such as bread and Chinese noodles, challenges such as dark color, rough texture, and poor solubility, and potential solutions that include modification methods. The primary purpose of this review is to comprehensively evaluate potential applications of dietary fibers in flour products, addressing common problems and reviewing potential solutions to promote further study and applications of dietary fibers.